UPAYA MENINGKATKAN PEMAHAMAN KONSEP BILANGAN DENGAN MENGGUNAKAN MEDIA PAPAN FLANEL PADA SISWA KELAS 2 DI SDN TEGUHAN 1 PARON NGAWI - RAHMAWATI, ANITA; Subayani, Nataria Wahyuning (JUSEDA, 2024)
One of the topics taught in lower grades is the mastery of unit, tens, and hundreds concepts. However, many teachers face difficulties in delivering these concepts effectively, including at SDN Teguhan 1 Paron Ngawi. Therefore, this study addresses this issue by employing flannel board media. With the use of flannel boards, students can effectively group unit, tens, and hundreds in their respective places. This research aims to enhance the understanding of number concepts among second-grade students at SDN Teguhan 1 Paron Ngawi using flannel board media. Understanding number concepts is crucial as it forms the foundation for mathematics learning at the elementary level and influences students' ability to comprehend more complex mathematical operations in the future. Flannel board media was chosen for its ability to provide concrete visual and manipulative experiences, aligning with the cognitive development characteristics of students at this age. The implications of this study include the development of more effective and inclusive mathematics teaching strategies, particularly within the context of basic education in Indonesia. The study recommends integrating flannel board media into the mathematics curriculum at SDN Teguhan 1 Paron Ngawi to enhance students' learning outcomes and deepen their understanding of number concepts.